Proapoptotic protein Bim attenuates estrogen-enhanced survival in lymphangioleiomyomatosis - Li, Chenggang (JCI Insight, 2016)
Lymphangioleiomyomatosis (LAM) is a progressive lung disease that primarily affects young women. Genetic evidence suggests that LAM cells bearing TSC2 mutations migrate to the lungs, proliferate, and cause cystic remodeling. The female predominance indicates that estrogen plays a critical role in LAM pathogenesis, and we have proposed that estrogen promotes LAM cell metastasis by inhibition of anoikis. We report here that estrogen increased LAM patient–derived cells’ resistance to anoikis in vitro, accompanied by decreased accumulation of the proapoptotic protein Bim, an activator of anoikis. The resistance to anoikis was reversed by the proteasome inhibitor, bortezomib. Treatment of LAM patient–derived cells with estrogen plus bortezomib promoted anoikis compared with estrogen alone. Depletion of Bim by siRNA in TSC2-deficient cells resulted in anoikis resistance. Treatment of mice with bortezomib reduced estrogen-promoted lung colonization of TSC2-deficient cells. Importantly, molecular depletion of Bim by siRNA in Tsc2-deficient cells increased lung colonization in a mouse model. Collectively, these data indicate that Bim plays a key role in estrogen-enhanced survival of LAM patient–derived cells under detached conditions that occur with dissemination. Thus, targeting Bim may be a plausible future treatment strategy in patients with LAM.